Maintenance versus replacement of medical equipment: a cost-minimization analysis among district hospitals in Nepal - Hillebrecht, Michael; Schmidt, Constantin; Saptoka, Bhim Prasad; Riha, Josef; Nachtnebel, Matthias; Bärnighausen, Till (BMC health services research, 2022)
About half of all medical devices in low- and lower-middle-income countries are currently non-operational because equipment maintenance is lacking. Thus, choosing a cost-efficient equipment maintenance approach has the potential to increase both the quantity and quality of important health services. Between 2010 and 2014 Nepal’s Ministry of Health chose two of its development regions to pilot the contracting-out of maintenance services to the private sector. We develop a cost model and employ different data to calculate the cost of this contracted-out scheme. The latter we compare with two additional common approaches to maintenance: in-house maintenance and no maintenance.